Flexural and Shear Behavior of FRP Strengthened AASHTO Type Concrete Bridge Girders - Nur Yazdani; Farzia Haque; Istiaque Hasan (Journal of Engineering)
Fiber-reinforced polymers (FRP) are being increasingly used for the repair and strengthening of deteriorated or unsafe concrete structures, including structurally deficient concrete highway bridges. The behavior of FRP strengthened concrete bridge girders, including failure modes, failure loads, and deflections, can be determined using an analytical finite element modeling approach, as outlined in this paper. The differences in flexural versus shear FRP strengthening and comparison with available design guidelines are also beneficial to design professionals. In this paper, a common AASHTO type prestressed concrete bridge girder with FRP wrapping was analyzed using the ANSYS FEM software and the ACI analytical approach. Both flexural and shear FRP applications, including vertical and inclined shear strengthening, were examined. Results showed that FRP wrapping can significantly benefit concrete bridge girders in terms of flexure/shear capacity increase, deflection reduction, and crack control. The FRP strength was underutilized in the section selected herein, which could be addressed through decrease of the amount of FRP and prestressing steel used, thereby increasing the section ductility. The ACI approach produced comparable results to the FEM and can be effectively and conveniently used in design.